Anxiety Assistance Mobile Apps Chatbot Using Cognitive Behavioural Therapy - Sulaiman, Suliana; Mansor, Marzita; Abdul Wahid, Rohaizah; Nor Azhar, Nur Anis Alisa (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
The current pandemic COVID-19 and lockdown have worsened patients' health, especially those who suffer from an anxiety disorder. However, anxiety disorders are treatable by undergoing different therapies treatment. This paper aims to develop an Anxiety Assistant Mobile Apps Chatbot (ANUVA) for university students using Cognitive Behavioural Therapy (CBT). Structured activities are used to motivate the user to question their thought distortions and change them back. The ANUVA chatbot is developed using Evolutionary Prototyping Model. The effectiveness of the ANUVA chatbot was tested using Confusion Matrix. The result indicates that the accuracy of the ANUVA chatbot is 75%, precision 85% and recall 88%. The System Usability Scale (SUS) test was used to measure the usability, and the score shows 86.75 for the result. For future work, all the chat records will link with the counselling unit system to enhance the efficiency of the therapies.